2006
DOI: 10.1158/1535-7163.mct-05-0293
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nuclear factor E2-related factor 2–mediated gene expression in mice liver and small intestine by cancer chemopreventive agent curcumin

Abstract: Curcumin has been shown to prevent and inhibit carcinogeninduced tumorigenesis in different organs of rodent carcinogenesis models. Our objective is to study global gene expression profiles elicited by curcumin in mouse liver and small intestine as well as to identify curcuminregulated nuclear factor E2-related factor 2 (Nrf2) -dependent genes. Wild-type C57BL/6J and Nrf2 knockout C57BL/6J/Nrf2(À/À) mice were given a single oral dose of curcumin at 1,000 mg/kg. Liver and small intestine were collected at 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(92 citation statements)
references
References 38 publications
5
87
0
Order By: Relevance
“…Several common clusters of genes such as that for ubiquitin/proteasome, cell adhesion, transcription factors were observed in this study that were also observed in previous studies with Nrf2 activators [9,33,[42][43][44] which validates our studies from a functional standpoint. In addition, three clusters of genes -calcium homeostasis, ER/Golgi transport & ER/Golgi biosynthesis/ metabolism genes, and glucose homeostasis genes -were uniquely observed as modulated via Nrf2 in response to TM-mediated ER stress that were not discernible in previous studies with Nrf2 activators.…”
Section: Discussionsupporting
confidence: 90%
“…Several common clusters of genes such as that for ubiquitin/proteasome, cell adhesion, transcription factors were observed in this study that were also observed in previous studies with Nrf2 activators [9,33,[42][43][44] which validates our studies from a functional standpoint. In addition, three clusters of genes -calcium homeostasis, ER/Golgi transport & ER/Golgi biosynthesis/ metabolism genes, and glucose homeostasis genes -were uniquely observed as modulated via Nrf2 in response to TM-mediated ER stress that were not discernible in previous studies with Nrf2 activators.…”
Section: Discussionsupporting
confidence: 90%
“…This hypothesis is supported by the beneficial effect of curcumin on CCl 4 -mediated liver fibrosis, 30 which may Nrf2 in liver fibrosis W Xu et al be at least in part mediated through activation of Nrf2 by this polyphenolic antioxidant. 39 In the future, some of these agents may potentially be used as supportive medication to reduce or even prevent toxin-induced liver fibrosis and possibly also to slow down its progression. Future studies will experimentally address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 activators have few common structural properties, but most or all of them react with thiols of Keap1 (Dinkova-Kostova et al, 2001). Many of these Nrf2 activators have been shown to be effective in experimental carcinogenesis models, and their chemopreventive actions are abolished in Nrf2-deficient mice, indicating that their effects are mediated by Nrf2 (Ramos-Gomez et al, 2001;Shen et al, 2006;Xu et al, 2006a;Yates et al, 2006). Several pharmacological and genetic studies have also demonstrated neuroprotective effects of Nrf2-activating phytochemicals in animal models of AD, PD, HD, and ALS (Burton et al, 2006;Jakel et al, 2007;Kraft et al, 2007;Kanninen et al, 2008Kanninen et al, , 2009Vargas et al, 2008;Chen et al, 2009c;Dumont et al, 2009;Yang et al, 2009b).…”
Section: A Adaptive Stress Responsesmentioning
confidence: 99%